2006
DOI: 10.1158/0008-5472.can-05-1818
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Inhibition of Intra-Peritoneal Tumor Growth and Dissemination of Human Ovarian Carcinoma Cells in Nude Mice by Anti-L1-Cell Adhesion Molecule Monoclonal Antibody Treatment

Abstract: The L1 cell adhesion molecule is implicated in the control of proliferation, migration, and invasion of several tumor cell types in vitro. Recently, L1 overexpression was found to correlate with tumor progression of ovarian carcinoma, one of the most common causes of cancer-related deaths in gynecologic malignant diseases. To evaluate L1 as a potential target for ovarian cancer therapy, we investigated the effects of anti-L1 monoclonal antibodies (chCE7 and L1-11A) on proliferation and migration of L1-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
140
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 38 publications
(42 reference statements)
12
140
0
Order By: Relevance
“…These results are in accordance with a recent report on efficient inhibition of intraperitoneal tumor growth and dissemination of human ovarian carcinoma cells in nude mice by L1-11A treatment. 17 However, we were unable to produce complete suppression of invasive melanoma growth in organotypic human skin culture, while staining with secondary antibody demonstrated that the added blocking antibody was present. These findings suggest that blockade of L1 adhesion molecule alone may not be sufficient to reverse invasive melanoma growth.…”
Section: Discussionmentioning
confidence: 74%
“…These results are in accordance with a recent report on efficient inhibition of intraperitoneal tumor growth and dissemination of human ovarian carcinoma cells in nude mice by L1-11A treatment. 17 However, we were unable to produce complete suppression of invasive melanoma growth in organotypic human skin culture, while staining with secondary antibody demonstrated that the added blocking antibody was present. These findings suggest that blockade of L1 adhesion molecule alone may not be sufficient to reverse invasive melanoma growth.…”
Section: Discussionmentioning
confidence: 74%
“…Recent studies have also implicated L1 in the aggressiveness of diff erent tumor types of nonneural origin such as colon cancer ( 24 ), melanoma ( 25 ), and ovarian carcinoma ( 21,26 ). However, the functional role of L1 in normal tissues outside the nervous system has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…S3 B). To evaluate the role of L1 in transendothelial migration, CFSE-labeled moDCs were pretreated with CE7, a monoclonal antibody that has been previously shown to neutralize L1 function ( 21 ), and then allowed to cross a monolayer of TNF-␣ -activated human umbilical vein ECs (HUVECs). The inactivation of L1 in moDCs with CE7 resulted in a dramatic reduction of the transendothelial migration as compared with moDCs treated with an irrelevant antibody ( Fig.…”
Section: Generation Of Conditional L1 Knockout Mice and Characterizatmentioning
confidence: 99%
See 1 more Smart Citation
“…The BLJ may thus be an important target for anti-cancer therapeutics because it can be manipulated from the cell surface, and is sufficient to suppress epithelial invasion. As a precedent for this idea, antibodies to L1, a human ortholog of Nrg, suppress ovarian epithelial cancer dissemination (Arlt et al, 2006). Future work will determine the degree to which the BLJ is sufficient to suppress epithelial invasion in other tissues and organisms.…”
Section: Relevance To Human Carcinoma Invasionmentioning
confidence: 99%